Sleep & Circadian Health are Associated with Mood & Behavior in Adolescents with Overweight/Obesity. Issue 4 (3rd July 2020) - Simon, Stacey L.; Diniz Behn, Cecilia; Laikin, Andrea; Kaar, Jill L.; Rahat, Haseeb; Cree-Green, Melanie; Wright, Kenneth P.; Nadeau, Kristen J.
ABSTRACT: Objective/Background: Rates of overweight/obesity and insufficient/delayed sleep are high among adolescents and are also unique risk factors for mood/behavior difficulties. This study aimed to evaluate relationships between sleep/circadian health and mood/behavior in a cohort of adolescents with overweight/obesity. Participants: Twenty-two adolescents (16.4 ± 1.1 years) with overweight/obesity attending high school completed in the study. Methods: Participants completed one week of home sleep monitoring (actigraphy), questionnaires assessing chronotype (diurnal preference; Morningness/Eveningness Scale for Children) and mood/behavior (Strengths & Difficulties Questionnaire), and had in-laboratory salivary melatonin sampling on a Thursday or Friday during the academic year. Results: Linear regressions revealed later weekday bedtime and shorter weekday time in bed and sleep duration were associated with worse mood/behavior scores. Shorter duration of melatonin secretion and greater "eveningness" were also associated with worse mood/behavior scores. Conclusions: Short and late sleep, shorter melatonin secretion, and eveningness chronotype are associated with worse mood/behavior symptoms in a cohort of adolescents with overweight/obesity. Clinicians should assess for both sleep and mood/behavior symptoms and further research is needed to evaluate the impact of improved sleep on mood/behavior in adolescents with overweight/obesity.